The effect of maternal breast variations on neonatal weight gain in the first seven days of life - Esmaeili Abbas; Darakhshan Shokoofeh; Vazirinejad Reza; Hadadian Shiva (BMC, 2009)
Abstract Background This study aims to examine whether specific maternal breast variations (such as flat nipple, inverted nipple, large breast or/and large nipple) are barriers for weight gain in breastfed infants during the first seven days of life. Methods In this prospective cohort study, 100 healthy term neonates were followed from birth to day seven in two groups; Group A: fifty neonates born to mothers with specified breast variations and Group B: fifty neonates born to mothers without such breast variations ("normal breasts"). All neonates were the first child of their families and there was no sex ratio difference between the two groups. Neonates' weight at birth and day seven were measured and the mean weight differences in the two groups were compared using paired t-test. Results Neonates born to mothers without the specified breast variations had a mean weight gain of (+) 53 ± 154.4 g at day seven., Not only there was no increase in the mean weight of neonates in the other group, but they had a mean decrease of weight of (-) 162 ± 125.5 g by the seventh day of their life compared to birth weight. Thus, neonates born to mothers without breast variations had significantly greater weight gain than neonates born to the mothers with the specified variations (p < 0.01). Conclusion Breast variation among first-time mothers acts as an important barrier to weight gain among breastfed neonates in the early days of life. Health professionals need skills in the management of breastfeeding among mothers with the specified breast variations, so that mothers are given appropriate advice on how to breastfeed and overcome these problems.